Kodifikasi dan Reformasi Hukum Keluarga di Maroko - Ade Risfal Huda; Ahmad Rezy Meidina (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
The Moroccan Constitution has declared itself a sovereign Muslim state with Islam as a religious State, but guarantees freedom of thought, opinion and belief as a fundamental feature of Sunni Maliki Muslims. Morocco is a country in Africa where the majority of the population is Muslim. Family law in Morocco established a new legal codification in 2004, which became known as Mudawwwanah al-Ahwal al-Sykahsiyyah al-Jadidah. This law is a revision of the existing law. The law consists of 400 articles, there is an additional 100 articles. Morocco is a country that has taken opinions from various schools of thought to determine the laws contained in Morocco which were then codified and developed according to the circumstances and conditions at that time so that a new law was born called Mudawwahan al-Usrah. Keywords: codification and reform, family law, Morocco